Using Indonesian as Language Use and Language Instruction in English Teaching for Non-EFL Students in ITB AAS Indonesia - Fitria, Tira Nur (Universitas Islam Negeri Alauddin Makassar, 2023)
This study investigates the use of the Indonesian language as language use and instruction in English teaching for Non-EFL students in ITB AAS Indonesia. This research is descriptive qualitative. The result analysis shows that Indonesian (Bahasa Indonesia) is a language used and instruction used by an English lecturer. English lecturer uses Indonesian in explaining and emphasizing English materials of grammar/tenses to their students. 2) English lecturer uses Indonesian in instructing the students about giving tasks and preparing for the test. An English lecturer usually uses a mixture of two languages, for example, Indonesian and English because the students are not from the English department, but they are mostly from non-English majors. She has considered using Indonesian based on the conditions and requests of students. Besides, She also translates from Indonesian to English and vice versa during English teaching, so the students can understand what is being said. English can be an international language used and instructed in class, so students will have the opportunity to increase their English skills. However, it is also possible that students struggle to comprehend English said by their lecturers. Besides, the usage of Indonesian in English teaching is used by the lecturer for Non-EFL students to overcome challenges in their learning. The use of Indonesian in the English classroom is beneficial to the teaching-learning process, provided that it is not overused and does not become habitual. When the students are taught only in Indonesian fully, they cannot use and master English. This issue necessitates a flexible approach to language use while instructing students in an English classroom. For instance, the use of Indonesian is restricted to the instruction of specific topics, such as grammar and vocabulary, while the use of English is restricted to the instruction of particular subject skills, such as pronunciation.